Manajemen Evaluasi Program Supervisi Pendidikan Dalam Meningkatkan Mutu Pendidikan - Abd. Wahib (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This paper will describe the conceptual foundation for evaluation management of educational supervision programs. The evaluation management of the educational supervision program is one of the keys to improving the quality of education in terms of quality which will give a characteristic to the evaluation of education itself, the background of the need for management of evaluation of the education supervision program, the objectives of the evaluation of the educational supervision program, the principles of evaluation of the educational supervision program the process of evaluating the educational supervision program. Strengthening evaluation management must have a conceptual basis to understand the evaluation of educational supervision programs both macro and micro in order to improve the quality of education itself.